The Influence Of Employee Competence And Work Discipline On Service Quality And Its Impact On Community Satisfaction In The Affordable Food Movement Program - Mience.D.M Wetaku; Arief Setyawan (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the influence of employee competence and work discipline on service quality and its impact on community satisfaction in the Affordable Food Movement Program. The research method uses a quantitative approach with purposive sampling technique. The research population consists of people participating in the Affordable Food Movement Program, with a sample of 50 respondents. The analytical tool used is Structural Equation Modeling (SEM) with the assistance of Smart PLS software to test the causal relationships between variables. The research instrument uses a questionnaire that has been tested for validity and reliability. The research results show that employee competence has a positive and significant effect on service quality with a path coefficient of 0.512 (p<0.05). Work discipline has a positive and significant effect on service quality with a path coefficient of 0.467 (p<0.05). Employee competence has a positive and significant effect on community satisfaction with a path coefficient of 0.398 (p<0.05). Service quality has a positive and significant effect on community satisfaction with a path coefficient of 0.624 (p<0.05). These findings imply that improving employee competence and work discipline are crucial factors in enhancing service quality, which ultimately impacts the increase in community satisfaction in the Affordable Food Movement Program.